Analysis, design, and development of a web-based thesaurus manager for the Philippine Medical Thesaurus data entry and validation modeling and implementation - Chan, Allen R. (2003)
Data entry and validation is the heart of any thesaurus manager; it is at the same time the most essential and the most crucial. It is where the data should be thoroughly checked and rechecked so as not to inadvertently introduce defects into the system. In the development of such a thesaurus manager, it is imprudent and foolhardy to just jump right in into the implementation phase hoping the trial and error could make up for its poor design. Before any such implementation could be attempted, it is first necessary to lay down a solid foundation where all possible factors of fault and inaccuracy have already been taken into account. Thus, it was necessary to construct data flow diagram (DFD) for the data entry and validation component of the thesaurus manager for the Philippine medical thesaurus (PMT).The DFD was synthesized from the existing guidelines proposed by the ISO 2788:1985, ISO5964:1985 and NISO Z39.19:1993 standards; however, it was proven that they were still lacking and failed to consider certain instances which were encountered by the PMT researchers. The findings and the experiences of the PMT researchers were thus taken into account and integrated into the DFD. The result was a thorough logical process model capable of both anticipating errors and correcting them before their introduction into the system, but however still simple enough to be followed and applied by the most basic of encoders, designers, or implementers. A web-based thesaurus manager was also developed by this study; it was implemented through Microsoft C#, ASP.Net and SQL 2000 technology.